1995
DOI: 10.1111/j.1748-0361.1995.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Work Safety Efforts by Wisconsin Extension Agricultural Agents

Abstract: This study investigated the agricultural work-related safety and health programming of county-level cooperative extension agents who work through land grant universities to provide a range of educational programs to agricultural producers. A questionnaire was designed and administered to all 89 Wisconsin agriculture and agribusiness extension county faculty. The questionnaire obtained valid responses from 98.9 percent of the agents. Ninety percent of all agents conducted some occupational safety and health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In agriculture, this role of communicating and adapting expert knowledge appears to be done at least to some degree by extension agents, who often lie at the intersection between farmers and expert knowledge ( Juntti and Potter 2002). For example, one study found that safety information from extension agents tends to be more ''farmer friendly,'' emphasizing working around hazards rather than correcting hazards (Chapman et al 1995).…”
Section: Other Perspectives On Trustmentioning
confidence: 99%
“…In agriculture, this role of communicating and adapting expert knowledge appears to be done at least to some degree by extension agents, who often lie at the intersection between farmers and expert knowledge ( Juntti and Potter 2002). For example, one study found that safety information from extension agents tends to be more ''farmer friendly,'' emphasizing working around hazards rather than correcting hazards (Chapman et al 1995).…”
Section: Other Perspectives On Trustmentioning
confidence: 99%
“…From their perspective, productivity outweighs safety, which is perceived to slow productivity [7]. Any safety training materials need to be short and direct to appeal to the farm work force that resists manuals and lengthy training formats [8]. As Legault and Murphy, noted, "Maximize the information given with a minimal amount of text" [9].…”
Section: Roadblocks To Tractor Safety Through Technical Communicationmentioning
confidence: 99%
“…17 The educational offerings will include presentations on plant microbiology, early recognition of biothreat-related zoonoses and botanical diseases, pests related to biosecurity, the agricultural extension agent as county plant health doctor, and food supply safety.…”
Section: Veterinary Medicine and Agriculturementioning
confidence: 99%